Pulmonary Embolism in COVID-19 Patients: Which Diagnostic Algorithm Should We Use? - Porfidia, Angelo; Mosoni, Carolina; Talerico, Rosa; Porceddu, Enrica; Lupascu, Andrea; Tondi, Paolo; Landi, Francesco; Pola, Roberto (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Although pulmonary embolism (PE) is a frequent complication of the clinical course of COVID-19, there is a lack of explicit indications regarding the best algorithm for diagnosing PE in these patients. In particular, it is not clear how to identify subjects who should undergo computed tomography pulmonary angiography (CTPA), rather than simply X-ray and/or high resolution computed tomography (HRCT) of the chest. Methods: We retrospectively analyzed COVID-19 patients who presented to the Emergency Department (ED) of our University hospital with acute respiratory failure, or that developed acute respiratory failure during hospital stay, to determine how many of them had a theoretical indication to undergo CTPA for suspected PE according to current guidelines. Next, we looked for differences between patients who underwent CTPA and those who only underwent X-ray and/or HRCT of the chest. Finally, we determined whether patients with a confirmed diagnosis of PE had specific characteristics that made them different from those with a CTPA negative for PE. Results: Out of 93 subjects with COVID-19 and acute respiratory failure, 73 (78.4%) had an indication to undergo CTPA according to the revised Geneva and Wells scores and the PERC rule-out criteria, and 54 (58%) according to the YEARS algorithm. However, in contrast with these indications, only 28 patients (30.1%) underwent CTPA. Of note, they were not clinically different from those who underwent X-ray and/or HRCT of the chest. Among the 28 subjects who underwent CTPA, there were 10 cases of PE (35.7%). They were not clinically different from those with CTPA negative for PE. Conclusions: COVID-19 patients with acute respiratory failure undergo CTPA, X-ray of the chest, or HRCT without an established criterion. Nonetheless, when CTPA is performed, the diagnosis of PE is anything but rare. Validated tools for identifying COVID-19 patients who require CTPA for suspected PE are urgently needed.